Noninvasive positive pressure ventilation in the assessment of extrinsic tracheal stenosis. (3rd March 2022) - Fiorelli, Alfonso; Fiorito, Roberta; Messina, Gaetana; Leone, Francesco; Mirra, Rosa; Pace, Maria Caterina; Ferraro, Fausto; Caterina, Mario
Abstract: In patients with extrinsic tracheal stenosis caused by a mediastinal mass, an airway stent is a palliative measure to relieve airway obstruction. However, the self-expanding force of the stent may be insufficient to force a rigid stenosis. Our goal was to report a simple strategy to indirectly estimate the rigidity of the stenosis and predict airway patency after inserting the stent. Before the procedure, the inspiratory and expiratory flows and their ratio were evaluated under spontaneous breathing and after positive pressure ventilation generated by a facial mask. In patients with stenosis successfully treated with a stent (n = 11), we found significant changes in expiratory (2.3 ± 0.7 vs 2.8 ± 0.7; p = 0.03) and inspiratory (1.5 ± 0.6 vs 2.5 ± 0.9; p = 0.001) flows and a reduction of their ratio (1.4 ± 0.3 vs 1.1 ± 0.2; p = 0.01) whereas no significant changes were observed in patients (n = 2) whose stent failed to force the stenosis. In these cases, a tracheostomy was performed to assure ventilation. Our simple strategy may help physicians predict airway patency after stenting or plan alternative treatments in patients with rigid stenosis difficult to force by stenting. Abstract : Airway stenting is a palliative measure to assure ventilation in inoperable patients with extrinsic tracheal compression caused by a mediastinal mass [1].